Early discontinuation of empirical antibacterial therapy in febrile neutropenia: the ANTIBIOSTOP study. Issue 7 (3rd July 2018) - Le Clech, Lenaïg; Talarmin, Jean-Philippe; Couturier, Marie-Anne; Ianotto, Jean-Christophe; Nicol, Christophe; Le Calloch, Ronan; Dos Santos, Stéphanie; Hutin, Pascal; Tandé, Didier; Cogulet, Virginie; Berthou, Christian; Guillerm, Gaëlle
Abstract: Introduction: Immediate empirical antibiotic therapy is mandatory in febrile chemotherapy-induced neutropenia, but its optimal duration is unclear, especially in patients with fever of unknown origin (FUO). Objectives: The primary objective of this 20-month prospective observational study was to evaluate the feasibility and safety of short-term antibiotic treatment in afebrile or febrile patients exhibiting FUO, irrespective of their neutrophil count. The secondary objective was to describe the epidemiology of all episodes of febrile neutropenia. Methods: In the first phase of the study, empirical antibiotic therapy in FUO patients was stopped after 48 h of apyrexia, in accordance with European Conference on Infections in Leukaemia guidelines ( n  = 45). In the second phase of the study, antibiotics were stopped no later than day 5 for all FUO patients, regardless of body temperature or leukocyte count ( n  = 37). Results: Two hundred and thirty-eight cases of febrile neutropenia in 123 patients were included. Neither the composite endpoint ( p  = .11), nor each component (in-hospital mortality ( p  = .80), intensive care unit admission ( p  = 0.48), relapse of infection ≤48 h after discontinuation of antibiotics ( p  = .82)) differed between the two FUO groups. Violation of protocol occurred in 17/82 episodes of FUO without any major impact on statistical results. Twenty-six (57.3%) and 22 (59.5%) FUO episodes did not relapse during hospital-stay ( p  = 1), and nine (20%) and five (13.5%) presented another FUO, respectively. One hundred and fifty-six episodes of febrile neutropenia (65.5%) were clinically or microbiologically documented, including 85 bacteremia. Conclusions: These results suggest that early discontinuation of empirical antibiotics in FUO is safe for afebrile neutropenic patients.